The role of mass, equation of state, and superfluid reservoir in large pulsar glitches. Issue 4 (20th January 2020) - Montoli, A; Antonelli, M; Pizzochero, P M
ABSTRACT: Observations of pulsar glitches may provide insights on the internal physics of neutron stars and recent studies show how it is in principle possible to constrain pulsar masses with timing observations. The reliability of these estimates depends on the current uncertainties about the structure of neutron stars and on our ability to model the dynamics of the superfluid neutrons in the internal layers. We assume a simplified model for the rotational dynamics of a neutron star and estimate an upper bound to the mass of 25 pulsars from their largest glitch and average activity: the aim is to understand to which extent the mass constraints are sensitive to the choice of the unknown structural properties of neutron stars, like the extension of the superfluid region and the equation of state. Reasonable values, within the range measured for neutron star masses, are obtained only if the superfluid domain extends for at least a small region inside the outer core, which is compatible with calculations of the neutron S -wave pairing gap. Moreover, the mass constraints stabilize when the superfluid domain extends to densities over nuclear saturation, irrespective of the equation of state tested.